The Classification of Emotions in the Character Key in the Novel Sucinya Cinta Sungai Gangga by Halimah Munawir: A Study from the Perspective of David Krech - Firdaus, Roqi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
The problem addressed in this research is how to classify the emotions of the character Key in the novel "Sucinya Cinta Sungai Gangga" by Halimah Munawir: a study from David Krech's perspective. This study aims to describe the classification of Key's emotions in the novel "Sucinya Cinta Sungai Gangga" by Halimah Munawir: a study from David Krech's perspective. This research is a qualitative descriptive study. The data used in this study are written data obtained from observing the character Key in the novel "Sucinya Cinta Sungai Gangga" by Halimah Munawir, which reflects the classification of emotions from David Krech's perspective. The data source for this research is the novel "Sucinya Cinta Sungai Gangga" by Halimah Munawir, published by Gramedia Pustaka Utama in 2013, with 217 pages. The data collection method used in this study is literature review and note-taking technique. The data in this study were analyzed using data analysis techniques by identifying, classifying, analyzing, and drawing conclusions. The results of this research indicate that there are four classifications of emotions from David Krech's perspective in the character Key in "Sucinya Cinta Sungai Gangga" by Halimah Munawir. These classifications of emotions are emotions related to sensory stimuli (primary emotions), self-related emotions, emotions related to sensory stimuli, and emotions related to others. They are further specified as feelings of guilt, happiness, shame, sadness, anger, and love. The most dominant classification of emotions in the character Key is the classification of sadness, while the weak classification of emotions in the character Nathan is the concept of guilt. It is hoped that this research can provide input for studying and developing research related to the theory of emotion classification from David Krech's perspective.